2020
DOI: 10.21203/rs.3.rs-31834/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shortlisting Phytochemicals Exhibiting Inhibitory Activity against Major Proteins of SARS-CoV-2 through Virtual Screening

Abstract: Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) declared as a pandemic by WHO that has affected more than 40 lakh peoples and caused death of more than 2 lakh individuals across the globe. Limited availability of genomic information of SARS-CoV-2 and non-availability of vaccines and effective drugs are major problems responsible for the ineffective control and management of this pandemic. Several attempts have been made to explore repurposing existing drugs known for their anti-viral activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…Competitive binding to viral spike protein by such SA-rich agents as gangliosides [ 41 ] and fetuin [ 80 ], for example, has been studied. Toward the goal of identifying potential therapeutics for COVID-19, four molecular modeling studies collectively screened over 800 molecules for binding to SARS-CoV-2 viral spike protein [ 193 , 194 , 195 , 196 ]. The strongest or close to strongest binding affinity in each study was obtained for ivermectin (IVM), a macrocyclic lactone with multifaceted antiparasitic and antimicrobial activity, distributed in 3.7 billion doses for human diseases worldwide since 1987 [ 197 , 198 , 199 ].…”
Section: Testing For Hemagglutination Caused By Sars-cov-2 Spike and ...mentioning
confidence: 99%
“…Competitive binding to viral spike protein by such SA-rich agents as gangliosides [ 41 ] and fetuin [ 80 ], for example, has been studied. Toward the goal of identifying potential therapeutics for COVID-19, four molecular modeling studies collectively screened over 800 molecules for binding to SARS-CoV-2 viral spike protein [ 193 , 194 , 195 , 196 ]. The strongest or close to strongest binding affinity in each study was obtained for ivermectin (IVM), a macrocyclic lactone with multifaceted antiparasitic and antimicrobial activity, distributed in 3.7 billion doses for human diseases worldwide since 1987 [ 197 , 198 , 199 ].…”
Section: Testing For Hemagglutination Caused By Sars-cov-2 Spike and ...mentioning
confidence: 99%
“…Further, prolonged durations of exposure to a drug likely would require a fraction of the dosing in short term cell model exposure. Further, multiple co-existing or alternate mechanisms of action likely explain the clinical effects observed, such as the competitive binding of ivermectin with the host receptor-binding region of SARS-CoV-2 spike protein, as proposed in six molecular modeling studies (Dayer, 2020;Hussien and Abdelaziz, 2020;Lehrer and Rheinstein, 2020;Maurya, 2020;Nallusamy et al, 2020;Suravajhala et al, 2020). In four of the studies, ivermectin was identified as having the highest or among the highest of binding affinities to spike protein S1 binding domains of SARS-CoV-2 among hundreds of molecules collectively examined, with ivermectin not being the particular focus of study in four of these studies (Scheim, 2020).…”
Section: Pre-clinical Studies Of Ivermectin's Activity Against Sars-cov-2mentioning
confidence: 99%
“…When we look at Table 7 which contains the values of binding energy of our molecule and other published inhibitors such as: HDZPA [57] , M1BZP [58] , Hydroxychloroquine [59] and moroxydine [4] with the same receptors. We find that these results give a clear view that 3-Cl BHB has the lowest values of the bending energy compared to the rest of the drugs, which confirms that our ligand have the stronger binding affinity towards M pro and RdRp of SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%